Global prevalence of intestinal parasites in cancer patients: a systematic review and meta-analysis - Yenesew Mihret Wondmagegn; Abebaw Setegn; Getu Girmay; Wagaw Abebe; Nega Dessie; Agenagnew Ashagre; Adane Derso; Adane Adugna; Mebratu Tamir; Tena Cherkos; Birhanu Malede; Banchayehu Getnet; et al. (BMC Infectious Diseases)
Abstract Background Intestinal parasite infections (IPIs) are a major cause of diarrhea and serve as a critical factor in infections affecting both immunocompetent and immunocompromised individuals. Opportunistic infections, in particular, present substantial challenges for those who are immunocompromised, such as cancer patients undergoing treatment. Therefore, this review aimed to assess the overall prevalence of these parasites in this vulnerable population worldwide. Methods We conducted a search across several databases, including PubMed, Medline, EMBASE, Web of Science, African Journals Online, the Cochrane Library, and Google Scholar. The protocol for this study was registered with the International Prospective Register of Systematic Reviews (PROSPERO; CRD42024621432) and was carried out in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Data analysis was performed using STATA version 11.0 software, employing a random-effects model to estimate the pooled prevalence of intestinal parasites among cancer patients, along with a 95% confidence interval. To address sources of heterogeneity across studies, we conducted subgroup and sensitivity analyses. The presence of publication bias was assessed using a funnel plot and Egger’s test statistic. A P-value of less than 0.05 was considered statistically significant. Results We identified 34 eligible studies on intestinal parasites among cancer patients, covering a total of 4,752 participants. The overall prevalence of intestinal parasites among cancer patients was found to be 28.42% (95% CI: 22.22–34.63) with a significant heterogeneity (I² = 97.5%, p = 0.000). Subgroup analysis indicated that patients with solid tumors had the highest prevalence of intestinal parasites at 31.13% (95% CI: 23.93–38.34), while those with mixed tumors had the lowest prevalence at 23.26% (95% CI: 13.96–53.95). Moreover, studies utilizing culture and PCR techniques revealed the highest prevalence of intestinal parasites, reported at 54.70% (95% CI: 46.39–63.00). Conclusion Based on the available studies, this meta-analysis revealed a substantial prevalence of intestinal parasites among cancer patients across the globe. The presence of intestinal parasites in immunocompromised individuals poses significant diagnostic and therapeutic challenges. Thus, the findings underscore the need for targeted interventions, and further research is needed to develop effective control strategies to reduce the impact of these illnesses on public health worldwide. Clinical trial number Not applicable